4-1BB co-stimulation further enhances anti-PD-1-mediated reinvigoration of exhausted CD39+ CD8 T cells from primary and metastatic sites of epithelial ovarian cancers - SungHoon Kim; Sang Wun Kim; Su-Hyung Park; Eui-Cheol Shin; Galam Leem; Junsik Park; Minwoo Jeon; Eui-Soon Kim; Yong Jae Lee; Seong Jin Choi; Baekgyu Choi; Seongyeol Park; et al. (Journal for ImmunoTherapy of Cancer)
Background Responses to immunotherapy vary between different cancer types and sites. Here, we aimed to investigate features of exhaustion and activation in tumor-infiltrating CD8 T cells at both the primary and metastatic sites in epithelial ovarian cancer.Methods Tumor tissues and peripheral blood were obtained from 65 patients with ovarian cancer. From these samples, we isolated tumor-infiltrating lymphocytes (TILs) and peripheral blood mononuclear cells. These cells were used for immunophenotype using multicolor flow cytometry, gene expression profile using RNA sequencing and ex vivo functional restoration assays.Results We found that CD39+ CD8 TILs were enriched with tumor-specific CD8 TILs, and that the activation status of these cells was determined by the differential programmed cell death protein 1 (PD-1) expression level. CD39+ CD8 TILs with high PD-1 expression (PD-1high) exhibited features of highly tumor-reactive and terminally exhausted phenotypes. Notably, PD-1high CD39+ CD8 TILs showed similar characteristics in terms of T-cell exhaustion and activation between the primary and metastatic sites. Among co-stimulatory receptors, 4-1BB was exclusively overexpressed in CD39+ CD8 TILs, especially on PD-1high cells, and 4-1BB-expressing cells displayed immunophenotypes indicating higher degrees of T-cell activation and proliferation, and less exhaustion, compared with cells not expressing 4-1BB. Importantly, 4-1BB agonistic antibodies further enhanced the anti-PD-1-mediated reinvigoration of exhausted CD8 TILs from both primary and metastatic sites.Conclusion Severely exhausted PD-1high CD39+ CD8 TILs displayed a distinctly heterogeneous exhaustion and activation status determined by differential 4-1BB expression levels, providing rationale and evidence for immunotherapies targeting co-stimulatory receptor 4-1BB in ovarian cancers.